COVID-19 Driven Adaptations in the Provision of School Meals in the Baltic Sea Region - Ala-Karvia, Urszula; Góralska-Walczak, Rita; Piirsalu, Evelin; Filippova, Ekaterina; Kazimierczak, Renata; Post, Anna; Monakhov, Valerii; Mikkola, Minna (Frontiers in Sustainable Food Systems, 2022)
The instability, rapid changes, and restrictions generated by the COVID-19 pandemic tested the provision of school meals in the Baltic Sea Region (BSR). School meal services were affected by factors such as full or partial lockdowns, strict hygiene regimes, lay-offs or staff shortages, stressful working environments, supply shortages, and changes to storing, cooking, and serving models. However, the responses to the COVID-19 crisis were highlighted by innovation, new opportunities, and cooperation. This paper reviews several examples of COVID-19 crisis management at school canteens in five BSR countries (Estonia, Finland, Poland, Russia (Saint Petersburg), and Sweden) between March 2020 and March 2021. The paper reveals the significant operational, logistical, and systemic problems that appeared because of the pandemic; the solutions and adaptations that were developed are also identified. The preparatory processes, logistics, and services that were adapted during the COVID-19 pandemic resulted in a new school meal provision model - a takeaway model; that includes similar features and unique characteristics across the different countries. Overall, the provision of school meals was carried out successfully in the BSR during the pandemic. Responsible, competent, and innovative professionals used their organizational skills, flexibility, and responsiveness to feed school pupils in a highly restricted and rapidly changing environment. It is expected that several of the COVID-19-driven innovations will remain in use following the pandemic.